An interaction design model for virtual reality mindfulness meditation using imagery‐based transformation and positive feedback - She, Yingying; Wang, Qing; Liu, Fang; Lin, Lin; Yang, Baorong; Hu, Bin (Computer animation and virtual worlds, 2023)
In recent years, mindfulness meditation has become increasingly popular as a way to relieve negative emotions. Although many studies have shown the advantages of the most immersive virtual reality (VR) technologies to support mindfulness meditation, few have summarized a standardized process for developing a VR tool to aid mindfulness meditation. We propose an interaction design model for VR mindfulness meditation using imagery‐based transformation and positive feedback to help users quickly soothe their negative emotions. Based on the traditional mindfulness meditation model, we propose the three detailed transformational steps to build (1) an interaction guidance process, (2) an interaction experience context, and (3) an interaction feedback mechanism. We build two scenarios based on them. Our experimental results suggest that our design can effectively alleviate a user's anxiety and provide emotional relief. Our insights on the transformation model of VR mindfulness meditation can be applied in related research, providing an effective reference model for VR mindfulness meditation systems, while providing new ideas for non‐pharmacological interventions in psychotherapy. We propose an interaction design model for virtual reality mindfulness meditation using imagery‐based transformation and positive feedback to help users quickly soothe their negative emotions. Based on the traditional mindfulness meditation model, we propose the three detailed transformational steps to build (1) an interaction guidance process, (2) an interaction experience context, and (3) an interaction feedback mechanism.